2018
DOI: 10.2147/ott.s173244
|View full text |Cite
|
Sign up to set email alerts
|

H19 induced by oxidative stress confers temozolomide resistance in human glioma cells via activating NF-κB signaling

Abstract: BackgroundRecent findings around long noncoding RNAs (lncRNAs) have opened novel areas of research around their prospective use in overcoming chemoresistance. Herein, we aimed to investigate the role of lncRNA H19 in temozolomide (TMZ) resistance of human glioma cells and the possible mechanisms.MethodsShort-/long-term oxidative stress was induced, and TMZ-resistant glioma cells (U251TMZ and LN229TMZ) were established. Small interfering RNA (siRNA) and overexpression plasmids were used to modulate the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…lncRNA H19 is located on chromosome 11 in humans and has been characterized as an oncogenic lncRNA in a few types of cancer due to its promotion of cell proliferation and chemoresistance (15)(16)(17). In the present study, we first found that H19 expression is negatively related to sorafenib sensitivity in HCC cells based on CCK-8 and EdU assays.…”
Section: Discussionmentioning
confidence: 54%
“…lncRNA H19 is located on chromosome 11 in humans and has been characterized as an oncogenic lncRNA in a few types of cancer due to its promotion of cell proliferation and chemoresistance (15)(16)(17). In the present study, we first found that H19 expression is negatively related to sorafenib sensitivity in HCC cells based on CCK-8 and EdU assays.…”
Section: Discussionmentioning
confidence: 54%
“…In the article, it was found that lncRNA growth arrest-specific transcript 5 (GAS5) activated NF-κB signaling pathway and enlarged nerve cell damage via downregulation of miR-124 [ 37 ]. What is more, the regulatory effects of lncRNA H19 on NF-κB signaling pathway have been excavated in various cancers, such as human osteosarcoma [ 38 ], gastric cancer [ 39 ], melanoma [ 40 ], and glioma [ 41 ]. In cancer progression, lncRNA H19 exerted a positive function on the activation of NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…H19 plays a critical role in the differentiation of many vital organs [25] . H19 may regulate the occurrence and development of tumors, such as breast carcinoma, bladder carcinoma, glioma and colorectal carcinoma [26][27][28] . Significantly, H19 can promote the differentiation of numerous types of cells, such as human mesenchymal stem cells (hMSCs) [29,30] , skeletal muscle satellite cells [31] and myoblasts [32] .…”
Section: Discussionmentioning
confidence: 99%